Present practice and future prospect of rooftop farming in Dhaka city: A step towards urban sustainability - Mastura Safayet; Md. Faqrul Arefin; Md. Musleh Uddin Hasan (Journal of Urban Management, 2017)
Dhaka, the capital of Bangladesh is one of the most populated megacity in the world and the population growth in this city is extremely high. To support growing food demand of increasing population, food supply should be secure and sustainable. On the other hand, with the pace of urbanization built-up areas are increasing; hence supply of roof space is also increasing. Rooftop farming can provide solution to increased food demand and also can promote a sustainable and livable city. Local fresh and safe food can be ensured through roof gardens in Dhaka city. The aim of the study is to explore the present practice and challenges of rooftop farming that was encountered by practitioners. Mirpur and Mohammadpur areas have been selected as study areas. Two practitioners are interviewed and 60 non-practitioners are surveyed. Results show that rooftop farming can support environment by improving air quality, reducing carbon in the atmosphere and can benefit society by reducing storm water management cost. One of the significant findings from the non-practitioner survey is that maximum people are willing to practice rooftop farming and want to provide at least 50% of roof space for rooftop farming. Finally some recommendations have been suggested to improve rooftop farming practice and encourage more people to practice rooftop farming in future.
Keywords: 710; Environmental benefits; Food production; Rooftop farming; Urban agriculture; Urban sustainability